2008
DOI: 10.1073/pnas.0802966105
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NKCC2 by a chloride-sensing mechanism involving the WNK3 and SPAK kinases

Abstract: The Na ؉ :K ؉ :2Cl ؊ cotransporter (NKCC2) is the target of loop diuretics and is mutated in Bartter's syndrome, a heterogeneous autosomal recessive disease that impairs salt reabsorption in the kidney's thick ascending limb (TAL). Despite the importance of this cation/chloride cotransporter (CCC), the mechanisms that underlie its regulation are largely unknown. Here, we show that intracellular chloride depletion in Xenopus laevis oocytes, achieved by either coexpression of the K-Cl cotransporter KCC2 or low-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
244
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(258 citation statements)
references
References 43 publications
10
244
3
1
Order By: Relevance
“…The kinase WNK3 is absent from ORNs. Among the four WNK kinases, WNK3 shows the highest expression in the brain, and WNK3 is thought to act as a Cl − sensor involved in protecting cells from excessive Cl − accumulation (45)(46)(47). The absence of WNK3 from ORNs, the simple thermodynamic basis of NKCC1 activity seen in our transport assay, and the absence of the main neuronal Cl − exporter KCC2 (2) all illustrate that these neurons dispense with means for intracellular Cl − reduction and instead optimize Cl − accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase WNK3 is absent from ORNs. Among the four WNK kinases, WNK3 shows the highest expression in the brain, and WNK3 is thought to act as a Cl − sensor involved in protecting cells from excessive Cl − accumulation (45)(46)(47). The absence of WNK3 from ORNs, the simple thermodynamic basis of NKCC1 activity seen in our transport assay, and the absence of the main neuronal Cl − exporter KCC2 (2) all illustrate that these neurons dispense with means for intracellular Cl − reduction and instead optimize Cl − accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown using WNK3-18a that the D294A substitution not only prevents the positive or negative effects of WNK3 on NKCCs or KCCs, respectively, but completely reverses these effects of WNK3 (2,9,20,21). In the present study, we assessed the consequences of eliminating the catalytic activity in all WNK3 isoforms on their effects on the cotransporters.…”
Section: Effects Of the Catalytically Inactive Wnk3 Variants On The Cmentioning
confidence: 99%
“…10). WNK3 activates NKCCs by increasing their phosphorylation, even when cells are incubated in hypotonic medium, where normally they are inactivated (9,10,20,21). In contrast, the coexpression of KCCs with WNK3 completely inhibits KCC function, even when cells are exposed to a hypotonic medium, in which the KCCs are normally active and dephosphorylated (2,22).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Commonly, WNK3 may affect the function of NCC in the following two ways. On one hand, WNK3 can regulate the expression of NCC on the cell surface; and on the other hand it may also influence the function of NCC on the cell membrane by phosphorylation (Ponce-Coria et al, 2008). Our observation after immunofluorescence staining showed that normally NCC was mainly distributed on the Cos-7 cell membrane, with a small amount distributed in the cytoplasm ( Figure S2 in Supporting Information).…”
mentioning
confidence: 71%